2022
DOI: 10.3390/app12031266
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bimodal Water Retention Curve on the Unsaturated Shear Strength

Abstract: Changes in climatic conditions are expected globally resulting in a higher rainfall intensity and longer duration of rainfall. The increase in the rainwater infiltration into the soil contributes to many geotechnical issues, such as excessive settlement, retaining wall failure and rainfall-induced slope failures. These geotechnical problems could be mitigated by the improvement of the problematic soil with the incorporation of the unsaturated soil mechanic principles. Dual-porosity soils or soils with bimodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The transient SEEP/W analysis was selected, and the water table served for initial pore-water pressure and head conditions. The initial rate changed from 1 to 0.65 to improve the convergence rate in the iteration calculation [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transient SEEP/W analysis was selected, and the water table served for initial pore-water pressure and head conditions. The initial rate changed from 1 to 0.65 to improve the convergence rate in the iteration calculation [16].…”
Section: Methodsmentioning
confidence: 99%
“…There should be noted that the length of the top and bottom sides of the slope is 3 times the height of the slope. It is an appropriate value to avoid the effect of boundary conditions from the left side and right sides of the numerical model since raindrops may infiltrate to nearby soil on both sides [16]. Different angles and heights of slopes were used for further comparison.…”
Section: Methodsmentioning
confidence: 99%
“…This analysis reveals a direct relationship between matric suction and volumetric water content, whereby an increase in matric suction corresponds to a decrease in volumetric water content [13]. Furthermore, A. Satyanaga et al [14] have clarified that when measuring the water retention curve, it is crucial for the water volume to attain a state of equilibrium before increasing the matric suction to a higher level. The experiment demonstrated that a significant reduction in water volume is occasionally not consistent with the air entrance value of the specimen in terms of suction.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the shear strength of arable soil is governed by a range of soil properties, especially bulk density and water content [2,17]. Bulk density reflects the compactness of the soil's structure, and water content directly affects the Coulomb force, the van der Waals force between soil particles, as well as the connection mode and cementation between soil particles.…”
Section: Introductionmentioning
confidence: 99%
“…A portable CPT data measuring device that can quickly measure cone tip resistance and cone side pressure through one penetration operation was designed. Given that water content and bulk density have a clear influence on soil shear strength [2,17] and that they are easily obtained using the oven-drying method [35], these two soil properties were combined with the CPT data points for constructing the prediction models. To our knowledge, there are no studies that have explored predicting the soil shear strength parameters by combining CPT data and soil properties.…”
Section: Introductionmentioning
confidence: 99%